TECHNOLOGY OF OBTAINING POLYRIBOSYLRIBITOL PHOSPHATE AS AN ACTIVE PHARMACEUTICAL INGREDIENT FOR THE PRODUCTION OF POLYSACCHARIDE VACCINES - E. L. Salimova; A. D. Konon; V. P. Truhin; I. V. Krasilnikov (Фармация и фармакология (Пятигорск), 2018)
Despite the world practice, in the Russian Federation immunization against hemophilic infection is carried out only for the children from risk groups, which may be due to the lack of production of this vaccine in the Russian Federation. Therefore, the development of technology for the preparation of polyribosylribitol phosphate (PRP, the active substance of the Hib vaccine) remains relevant. Earlier, the employees of the federal state unitary enterprise “Saint-Petersburg scientific research institute of vaccines and serums and the enterprise for the production of bacterial preparations” of Federal medical and biologic agency of Russia isolated and identified the strain of Haemophilus influenzae SPB type b B-7884. The conditions for cultivation of the strain B-7884 and primary isolation of PRP from the culture liquid were arranged. The aim of the work was to study the possibility of excluding the centrifugation stage for separating H. influenzae SPB type b B-7884 biomass before clarification on the cascade of filter discs, and the development of subsequent stages of PRP isolation from the obtained intermediate product. Materials and methods. PRP isolation from an inactivated culture liquid of strain B-7884 was carried out by centrifugation, filtration, precipitation, homogenization, extraction under various conditions. The concentration of PRP in the intermediate products was determined by the orcinol method, the identity was determined by the latex agglutination test. Results and discussion. The optimal scheme for isolation and purification of the active pharmaceutical ingredient PRP, including filtration through the cascade of deep filters Zeta plus LP 60 (0.3–0.6 μm) and Zeta plus LP 90 (0.1–0.3 μm), concentration and diafiltration on ultrafiltration cassettes with nominal molecular weight cut-off of 30 kDa, precipitation with 10% cetyltrimethylammonium bromide solution (5% v/v), with subsequent homogenization of the obtained precipitate (in the presence of 12.5% of ethanol from the concentrate volume) and extraction (32.5% ethanol), filtration through depth filters Zeta Plus SP 30 and carbon filters Zeta Plus Carbon R53, and precipitation by 1.0% (v/v) 4.0 M sodium chloride solution and freezing at –(20 ± 2)°C, was developed. Conclusion. The obtained results will become the basis for the further development of the polysaccharide substance and allow us to proceed to the next stage in the development of the vaccine against Haemophilus influenzae type b – conjugation with the carrier protein.